Sustainability performance and financial performance in selected Johannesburg Stock of Exchange listed companies - Moswatsi, Kgorompe Michael (My University, 2022)
The corporate sustainability performance (CSP) journey is coupled with many complex issues which have subsequently eliminated the boundary between legal and discretionary social practices. In South African JSE SRI listed organisations, sustainability performance programmes are regarded as tools for redressing socioeconomic disparities. However, the influence of sustainability performance on organisations‟ financial performance becomes a vital notion in contemporary sustainable development debates as evidenced by extensive inconclusive literature that has its long roots in the research field. The aim of the study is to examine how corporate sustainability performance influences organisations‟ financial performance which is return on assets (ROA). Through content analysis, secondary data were extracted from annual integrated reports of 175 purposively sampled South African organisations registered on the Johannesburg Stock Exchange (JSE SRI Index) for the years 2009-2019. The study employs cross-sectional time series feasible generalised least regression (FGLS) to test the correlation between the dimensions of corporate sustainability performance and return on assets as a proxy for organisational financial performance. The study results confirm that employees‟ health and safety sustainability performance programmes have a significant and positive impact on return on assets, whereas CSP programmes in community social activities have a positive and significant influence on return on assets. An insignificant relationship exists between Eco-investments (socially responsible investments) and return on assets (ROA). The study concluded that there is a significant association between CSP and ROA. The findings further confirm that control variables (leverage ratio, current ratio, total assets turnover, operating profit margin and price earnings ratio) have an effect on the correlation between CSP and ROA. The results have potential implications for corporate sustainability performance policy makers in South Africa, and contribute to corporate sustainability performance/organisations‟ financial performance debate. The study further stresses that continuous review of CSP policies is imperative to ensure that sustainable business practices are achieved.
Thesis (M.COM. (Accounting)) -- University of Limpopo, 2022
Keywords: Organisation financial performance; Return on assets; Employees health and safety expenditure; Community social activities; Eco-investments; Performance -- Management; Performance standards; Stock exchanges